Building management system : a case study at Albukhary foundation head office - Abdul Rahman, Mohd. Rizal (2010)
The application of building management system is extremely important. Currently at Albukhary Foundation there is no systematic building management system being applied to manage the Albukhary Foundation Head office. In this context, this study aimed to investigate the importance and significance of the building management system in managing the maintenance systematically, so that the findings can be used as guidelines and additional information for other building management team. The objectives for this research are to study the current building management system at Albukhary Foundation Head Office, to identify the weakness to the current building management system and to propose an improvement to existing building management system through the establishment of Standard Operating Procedure for the maintenance department. The method of obtaining the information and data was carried out by referring to literature review, observation, documents study, interviews and survey with the relevant party whose directly involved with the maintenance of the building. The findings of the study are the current building management system found inadequate for achieving effective maintenance management of the building, the weaknesses of the current system among others include insufficient data to generate documented reports and minimizing the maintenance department response time, and the establishment of new building management system through the development of Standard Operating Procedure where the new developed Standard Operating Procedure model will act as a guideline for maintenance department as well as to assist the management in monitoring purposes and it is capable to be a basis for the development of sustainable policies in the future.